(untitled) (Bangladesh Journal of Neurosurgery, 2023)
The meninges are protective coverings around the whole central nervous system comprising of three layers, from outside inwards, Dura mater, Arachnoid mater and Pia mater. These three terms are derived from Latin, where ‘mater’ means mother. Why this motherhood has been implicated while naming these layers, carries a very interesting history and a strong philosophical background. Dura mater (Tough mother), Arachnoid mater (Spider-like mother) and Pia mater (Tender mother)-all of them cover the central nervous system and possess functional significance not less than that of a protective mother. Ancient Arabic scientists observed those facts and named them accordingly in Arabic. Later they were translated into Latin and are in practice till now. While studying various facts regarding the central nervous system, the etymology and philosophy of ‘maternalization of the meninges’ draws immense attention. Bang. J Neurosurgery 2022; 12(1): 3-5